A Validation Study of the General Amber Force Field Applied to Energetic Molecular Crystals. Issue 1 (2nd January 2016) - Bergh, Magnus; Caleman, Carl
Abstract : Molecula dynamics is a well-established tool to computationally study molecules. However, to reach predictive capability at the level required for applied research and design, extensive validation of the available force fields is pertinent. Here we present a study of density, isothermal compressibility and coefficients of thermal expansion of four energetic materials (FOX-7, RDX, CL-20 and HMX) based on molecular dynamics simulations with the General Amber Force Field (GAFF), and compare the results to experimental measurements from the literature. Furthermore, we quantify the accuracy of the calculated properties through hydrocode simulation of a typical impact scenario. We find that molecular dynamics simulations with generic and computationally efficient force fields may be used to understand and estimate important physical properties of nitramine-like energetic materials.